Photodiode based on GaP sensitized to short-wave region of UV spectrum - Dobrovol’skii, Yu. G. (Technology and design in electronic equipment, 2012)
An algorithm for the simulation and analysis of the parameters that determine the sensitivity of the photodiode surface-barrier structures based on n+–n-GaP–SnO2(F) has been developed. It has been shown that the monochromatic current sensitivity to radiation at wavelength of 250 nm in such a structure can reach 0,1–0,12 A/W.